Methods in cell biology. - Perez, Franck; Stephens, David J. (Methods in cell biology, 2013)
This volume looks at methods for analyzing of golgi complex function. Chapters cover such topics as in vitro reconstitution systems, fluorescence-based analysis of trafficking in mammalian cells and high content screening.